PENGARUH DOSIS STATIN TERHADAP KADAR LIPID PLASMA DAN OUTCOME FUNGSIONAL PADA PASIEN STROKE ISKEMIK - Franz Julius H*, Yuneldi Anwar*, Darulkutni Nasution* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION HIGH LEVEL OF CHOLESTEROL IS THE RISK FACTOR FOR ISCHEMIC STROKE EARLY TREATMENT WITH STATINS MAY REDUCE PLASMA LIPID LEVEL AND THEREFORE IMPROVE OUTCOMES OF ACUTE ISCHEMIC STROKE